PENGARUH PENERAPAN MEDIA PEMBELAJARAN ULAR TANGGA TERHADAP MOTIVASI BELAJAR PKn SISWA KELAS VIII SMP NEGERI 1 LUBUK DALAM KABUPATEN SIAK - Titin Rohaini Titin Rohaini; Zahirman Zahirman '; Sri Erlinda Sri Erlinda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study was motivated by the lack of student motivation toward particular subjects Civic Education in SMPN 1 Lubuk Dalam. Formulation of the problem in this research is: "How does the application of learning media snake ladder on motivation to learn civics class VIII SMPN 1 Lubuk Dalam Siak?". This study aims to determine students' motivation to learn civics class VIII SMPN 1 Lubuk Dalam Siak after learning media snakes. This research was conducted in SMP Negeri 1 Lubuk Dalam Siak in May 2015. This research is descriptive quantitative population in this research is class VIII SMP Negeri 1 Lubuk Dalam Siak. Sampling was done by the technique of "purposive sampling". Where classes are taken into the sample is class VIII B (experimental class) is treated by using instructional media snake ladder and VIII D (control group) were treated with lecture, then the data analysis using the homogeneity test, test "t" and Test influence. Based on the results of the study showed that there is influence students' motivation to use snake ladder and lecturing in SMP Negeri 1 Lubuk Dalam Siak (t = 10.15> table = 2.00 with 62% coefficient of influence). Where there is an average increase motivation to learn civics class control of 19.28, become 19,90 in first time, 20,87 second time, into 21.59 in last time and an average increase motivation to learn civics class experiment of 19.93, become 24,75 in first time, 26,09 in second time, into 26.97 in last time. Means the hypothesis which says the use of instructional media snake ladder effect Motivation Learning Civic Education class VIII student at SMPN 1 Lubuk Dalam Siak accepted.Keywords: Media Education Snakes and Ladders, Motivation.